Six new species of Triomicrus Sharp from southern China (Coleoptera: Staphylinidae: Pselaphinae) - Shen, Jia-Wei; Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
Seven species of the genus Triomicrus Sharp are recognized in southern China, six of them are described as new: T. acutus  and T. nanlingensis Shen & Yin, sp. n. (Guangdong), T. pinnatus Shen & Yin, sp. n. (Guangdong and Hunan), T. cochlis Shen & Yin, sp. n. (Guangdong, Hunan and Guangxi), and T. cavus Shen & Yin, sp. n. and T. longus Shen & Yin, sp. n. (Guangxi). A key for the identification of Triomicrus in southern China is presented.